1981
DOI: 10.1042/cs0600311
|View full text |Cite
|
Sign up to set email alerts
|

Total Body Potassium in Relation to Thyroid Hormones and Hyperthyroidism

Abstract: 1. Body weight and total body potassium were measured in 23 hyperthyroid patients before and at various stages during treatment and in 19 athyreotic patients who were being treated with high-dose L-thyroxine. 2. In the hyperthyroid patients the total body potassium rose by 23 +/- 2.8% (SEM) within a few weeks of restoring the blood thyroid hormone levels to normal. The body potassium values after treatment were close to that expected in these individuals if they were healthy indicating that a considerable loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Studies of changes in body composition following treatment for hyperthyroidism are conflicting. Some show that rises in BMI, total fat mass and total lean mass occur in parallel (Zimmerman‐Belsing et al ., 1998; Edmonds & Smith, 1981), others that weight gain after treatment reflects predominantly an increase in muscle and bone mass (Bayley et al ., 1980; De La Rosa et al ., 1997), while another shows that first muscle mass, then adipose tissue but not bone mass is increased (Lönn et al ., 1998). High circulating concentrations of leptin persist after normal body composition has been attained, and this may predispose to weight gain (Zimmerman‐Belsing et al ., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of changes in body composition following treatment for hyperthyroidism are conflicting. Some show that rises in BMI, total fat mass and total lean mass occur in parallel (Zimmerman‐Belsing et al ., 1998; Edmonds & Smith, 1981), others that weight gain after treatment reflects predominantly an increase in muscle and bone mass (Bayley et al ., 1980; De La Rosa et al ., 1997), while another shows that first muscle mass, then adipose tissue but not bone mass is increased (Lönn et al ., 1998). High circulating concentrations of leptin persist after normal body composition has been attained, and this may predispose to weight gain (Zimmerman‐Belsing et al ., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Established body composition evaluation techniques in a previous study showed that the loss of bone mineral content and MM was predominant in typical hyperthyroidism (37). In another study, it was shown that the free-fat mass was more sensitive to thyroid hormones than the body fat mass (38). During treatment, patients who developed hypothyroidism had a larger weight gain than those who did not (6).…”
Section: Discussionmentioning
confidence: 97%
“…However, the results of studies examining alterations in body composition following treatment for Graves’ disease have been inconsistent. Several previous studies have compared changes in body composition in patients with hyperthyroidism due to Graves’ disease or toxic multinodular goiter pre- and post-treatment with antithyroid drugs (ATD) or radioactive iodine, showing increases in lean mass [ 5 ], fat mass [ 6 ], or both [ 1 , 2 , 7 - 9 ]. Furthermore, these changes in body composition have been reported to occur sequentially (muscle gain followed by fat gain or vice versa) [ 2 , 9 ] or concurrently [ 10 ].…”
Section: Introductionmentioning
confidence: 99%